The Effect Of Dividend Per Share , Earning Per Share & Debt To Equity Ratio On Stock Prices With Perceived Risk Of Stocks As Moderating Variables - Denny Kurnia (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
This study uses an empirical study for the Automotive and Spare Parts Subsector companies in Southeast Asia for the 2012-2019 period. The purpose of this study is to determine the analysis of Dividend Per Share (DPS), Earning Per Share (EPS) and Debt to Equity Ratio (DER) to Stock Prices moderated by Perceived Risk Shares. The data used in this study is secondary data from the Automotive and Spare Parts Sub-sector companies in Southeast Asia for the period 2012-2019. The sampling method was taken and produced 20 companies as samples. The statistical analysis used in this study is the analysis of moderated regression analysis (MRA), multiple linear regression, partial test and simultaneous test with SPSS version 21. The study concludes that all independent variables have an effect on stock prices but are not significant. Based on the results of the coefficient of determination test, the value of adjust R square is 25.2%, the remaining 74.8% is influenced by variables outside this study.